The Influence of Chatbot Information Systems on Customer Experience and Social Media Engagement in Marketplaces - Cempaka, Annisa Giwang; Hadiprawoto, Triana Rahajeng (Indonesian Journal of Business and Entrepreneurship, 2025)
Background: In the era of the e-commerce boom, the role of chatbots in enhancing customer experience and engagement on social media has become increasingly vital in the dynamics of the marketplace market and industry.Purpose: This research aims to investigate how the information quality, system quality, and service quality of chatbots influence customer satisfaction and positive emotions, leading to increased social media engagement.Design/Methodology/Approach: An online survey was conducted with 305 respondents who use chatbot services on marketplace platforms. Data collected from an online survey are analyzed against the research model using PLS-SEM.Findings/Results: The results show a positive impact and direct influence of information quality, system quality, and service quality on positive emotions and customer social media engagement, but no direct influence was found between satisfaction and customer social media engagementConclusions: The study indicates that the quality of chatbot information and service plays a crucial role in enhancing customer satisfaction and fostering positive experiences. Positive emotions, in turn, significantly drive customer engagement in activities such as co-developing and advocating on social media. Originality/Value (State of the Art): By focusing on the mediating role of positive emotions, the study offers a deeper understanding of how chatbots contribute to customer interaction and social media behavior. Keywords: chatbot services, information system, customer satisfaction, positive emotions, customer social media engagement.